Development of a HOG-based real-time PCR method to detect stress response changes in mycotoxigenic moulds. (August 2016) - Rodríguez, Alicia; Medina, Ángel; Córdoba, Juan J.; Magan, Naresh
Abstract: There is a need to understand the mechanism of adaptation of toxigenic fungal species which are able to colonise highly specialised foods such as cured meats where there is a high osmotic stress due to the presence up to 20–22% NaCl during the ripening process. A new tool able to detect changes in stress related genes would be useful to understand the ecological reasons for the ability of these species to grow in specialised niches. In this work a real-time PCR (qPCR) using SYBR Green was developed. Primers were designed from the Hog1 gene involved in osmo-adaptation in fungi. For this, conserved regions resulting from the alignment of 26 published partial sequences of such gene were used. Specificity of primers HogF2/R2 was demonstrated when amplified, producing a unique 131-bp PCR product with a Tm value of 84 °C. The qPCR method showed an efficiency of 98%, R 2 value > 0.99 and a detection limit of 0.7 log Hog1 gene copies. The qPCR method to measure changes in the Hog1 gene expression in relation to growth in ionic and non-ionic stressed environments (using 10–40% NaCl and sorbitol concentrations) was found to be suitable for two mycotoxigenic species ( Penicillium nordicum, P. expansum ). This assay will be a valuable tool for generating relevant Hog1 expression data from different mould species in relation to different stresses in food habitats. It will also be a good tool for a better understanding of the ability of xerophilic and xerotolerant species to colonise extreme environments. Highlights: A SYBR Green-based qPCR targets the Hog1 gene involved in osmo-adaptation in fungi. The designed qPCR shows high sensitivity and specificity. Changes in Hog1 gene expression are related to growth in osmotically stressed niches. RT-qPCR helps to understand the ability of some fungi to occupy stressed environments.